Prevalence of symptoms of pelvic floor dysfunction and related factors among Japanese female healthcare workers. Issue 5 (27th June 2022) - Sawai, Moe; Yuno, Chikako; Shogenji, Miho; Nakada, Harumi; Takeishi, Yoko; Kawajiri, Maiko; Nakamura, Yasuka; Yoshizawa, Toyoko; Yoshida, Mikako
Abstract: Objectives: Women working in the medical field may be at risk for pelvic floor dysfunction due to high physical activity levels leading to increased abdominal pressure; however, the actual situation remains unknown. This study aimed to clarify the prevalence of symptoms of pelvic floor dysfunction and its associated factors among Japanese women working in the medical field. Methods: A cross‐sectional study was conducted among female employees at a public hospital in Japan from July to August 2020. Participants answered a web‐based questionnaire. Three types of symptoms related to pelvic floor dysfunction were assessed based on one or more subscale scores in the Pelvic Floor Distress Inventory‐Short Form 20 (PFDI‐20). Results: Out of 466 female employees in the hospital, 294 responded (response rate 63.1%). The mean age was 42.8 ± 10.3 years old and 221 (73.5%) were nurses. The prevalence of at least one type of symptom was 63.9%. The prevalence of recto‐anal symptoms (45.9%) was highest, followed by lower urinary tract (37.1%) and pelvic organ prolapse symptoms (22.8%). The total PFDI‐20 score was associated with constipation (β = .254), body mass index (β = .136), and part‐time work (β = .167) after adjusting for other variables. Conclusion: This study showed a high prevalence of symptoms related to pelvic floor dysfunction among women working in the medical field. Lifestyle management to prevent constipation and obesity is a promising strategy to improve symptoms of pelvic floor dysfunction.